Microhabitats utilization by solitary parasitoids and predatory insects as indicators of oil palm agroecosystem’s capacity to support insect species diversity - Ahmad Bukhary A.K.,; Ruslan M.Y.,; Noor Hisham H.,; Muzamil M.,; Abu Hassan A.,; Idris A.B., (Penerbit Universiti Kebangsaan Malaysia, 2021)
Microhabitats capacity to support insect species diversity and persistence were evaluated implementing solitary parasitoids and predatory insects according to different phases of herbicide and chemical fertilizer applications. Two species of the genus Xanthopimpla (Ichneumonidae) and one species of the genus Pompilus (Pompilidae) showed relationships on vegetation-type microhabitats, notably natural weeds, leguminous cover crops, and the beneficial plant Turnera subulata, while two species of the genus Evania (Evaniidae) showed relationships with chipped oil palm trunks. One species from the genus Odontomachus (Formicidae) as an exclusive predatory ant was related to both chipped oil palm trunks and the beneficial plant T. subulata. Xanthopimpla parasitoids exhibited abundance fluctuations difference around natural weeds during herbicide application phases between three- and six-years old oil palm stands, with decreased and increased abundance patterns of the former and the latter, respectively. 18 years old oil palm stand showed increased abundance patterns only along with the different phases of chemical fertilizer applications. The importance of natural weeds diversity, restrictions of leguminous cover crops, frequency of herbicide applications, and the arrangements between beneficial plants and wood-based microhabitats that benefited insect parasitoids and predators were discussed.